Photodynamic Therapy From Basic Science to Clinical Research - Mayumi Inada, Natalia; Harb Buzzá, Hilde; Cristina Blanco, Kate; Danilo Dias, Lucas (IntechOpen, 2021)
Today, in the face of resistant microorganisms, aggressive cancers unresponsive to conventional treatments, and the COVID-19 pandemic, the need for advanced and innovative protocols for combating and treating disease is paramount. This book presents basic concepts of photodynamic therapy along with data from clinical research on its use in treating oncologic and other diseases. It also presents innovative strategies in photodynamic therapy, including information on polymer nanoparticles. This book was prepared with great care and by many valuable hands so that we can expand the dissemination of Photodynamic Therapy, as well as motivate for new research.